Green technology upgrade path for food supply chain enterprises: insights from grounded theory and fuzzy-set qualitative comparative analysis (fsQCA) - Lu, Lin; Ren, Yuelin; Dong, Ruihai; Li, Chaoling; Mao, Siyi (Frontiers in Sustainable Food Systems, 2025)
This study explores the green technology upgrade path for food supply chain enterprises using grounded theory and fuzzy-set qualitative comparative analysis (fsQCA). It identifies six key elements of food supply chain resilience: network centrality, network connectivity, network heterogeneity, resource bricolage, entrepreneurs’ attention to new food technologies, and their alertness to such technologies. A theoretical model is constructed, and a questionnaire is designed based on these findings. The fsQCA reveals that configurational thinking exists among the key drivers of technology upgrades, with network centrality as a core element. Entrepreneurs’ attention to external new food technologies significantly impacts technological transformation, and network centrality is a necessary condition for upgrades. The study finds that the interaction of network connectivity, resource bricolage, and entrepreneurial attention generates a multiplicative effect, accelerating technological upgrading. The results highlight the importance of network centrality and the dynamic evolution of factors influencing green technological upgrades. The findings offer new perspectives for future research and enterprise strategies, emphasizing the need for active construction of cooperative networks, intensified entrepreneur training, optimized resource assembly strategies, and sufficient financial support. Future research could explore how digital transformation influences these upgrade paths. Additionally, studying the impact of international cooperation and trade policies on green technology upgrades in food supply chains would be valuable.